A Simple & Convenient Solid Phase Synthesis of Bacterial Origin Octapeptide Sequence, Glu-Asp-Gly-Asn-Lys-Pro-Gly-Lys-OH - Khan, Riaz A. (Springer Netherlands, 2010)
The repeating octapeptide sequence, Glu-Asp-Gly-Asn-Lys-Pro-Gly-Lys-OH derived from the glycoprotein found in Staphylococcus aureus cell wall is assembled by simple solid phase peptide synthesis methodology using a base labile linker.